2019
DOI: 10.1111/evj.13122
|View full text |Cite
|
Sign up to set email alerts
|

Race performance following epiglottic entrapment surgery in Thoroughbred yearlings

Abstract: Summary Background Epiglottic entrapment can occur in yearling Thoroughbreds (TB); however, race performance following surgical correction is unknown. Objectives To determine the race performance of horses treated surgically for epiglottic entrapment as yearlings as compared to an untreated cohort. A second objective was to identify risk factors for treated horses not racing post‐operatively. Study design Retrospective cohort and case–control studies. Methods Medical (1989–2014) and race records of 66 treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…This retrospective study by Alexandra Curtiss and colleagues in the USA aimed to evaluate the racing performance of horses treated surgically for epiglottic entrapment as yearlings compared to their maternal half‐siblings .…”
Section: Epiglottic Entrapmentmentioning
confidence: 99%
“…This retrospective study by Alexandra Curtiss and colleagues in the USA aimed to evaluate the racing performance of horses treated surgically for epiglottic entrapment as yearlings compared to their maternal half‐siblings .…”
Section: Epiglottic Entrapmentmentioning
confidence: 99%
“…A retrospective study of epiglottic entrapment identified and treated in 66 Thoroughbred yearlings supports early diagnosis and treatment of URT disorders . Investigating whether yearlings diagnosed and surgically treated for epiglottic entrapment were less likely to race as compared to maternal half‐siblings with no identified URT abnormalities, medical and racing records were reviewed, with pre‐ and post‐surgical endoscopic images available for most horses.…”
mentioning
confidence: 99%